Should metformin remain the first-line therapy for treatment of type 2 diabetes?. (January 2021) - Baker, Chelsea; Retzik-Stahr, Cimmaron; Singh, Vatsala; Plomondon, Renee; Anderson, Victoria; Rasouli, Neda
Metformin is a biguanide that is used as first-line treatment of type 2 diabetes mellitus and is effective as monotherapy and in combination with other glucose-lowering medications. It is generally well-tolerated with minimal side effects and is affordable. Although the safety and efficacy of metformin have been well-established, there is discussion regarding whether metformin should continue to be the first choice for therapy as other anti-hyperglycemic medications exhibit additional advantages in certain populations. Despite a long-standing history of metformin use, there are limited cardiovascular outcomes data for metformin. Furthermore, the available studies fail to provide strong evidence due to either small sample size or short duration. Recent data from glucagon-like peptide-1 receptor agonist and sodium-glucose cotransporter-2 inhibitor cardiovascular and renal outcomes trials demonstrated additional protection from diabetes complications for some high-risk patients, which has impacted the guidelines for diabetes management. Post-hoc analyses comparing hazard ratios for participants taking metformin at baseline versus not taking metformin are inconclusive for these two groups. There are no data to suggest that metformin should not be initiated soon after the diagnosis of diabetes. Furthermore, the initiation of newer glycemic-lowering medications with cardiovascular benefits should be considered in high-risk patients regardless of glycemic control or target HbA1c. However, cost remains a major factor in determining appropriate treatment.